2022
DOI: 10.3390/ani12010123
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sodium Humate on the Growth Performance, Diarrhea Incidence, Blood Parameters, and Fecal Microflora of Pre-Weaned Dairy Calves

Abstract: This study aimed to evaluate the effects of the administration of sodium humate (NaH) on the growth performance, diarrhea incidence, and fecal microflora of pre-weaned Holstein calves. In a 53-day experiment, forty healthy newborn female calves were randomly allocated to the following four treatment groups: (1) control (basal diet); (2) 1-gram NaH (basal diet extra orally supplemented with 1 g of NaH dissolved in 100 mL of milk or milk replacer daily); (3) 3-gram NaH (basal diet extra orally supplemented with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 46 publications
4
4
0
Order By: Relevance
“…Haematological indices and serum metabolite levels reflect the health status of animals, and in the present study, these parameters were within the normal ranges for healthy calves (Alugongo et al, 2017;Maldonado et al, 2018;Slanzon et al, 2019;D. Wang et al, 2022).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Haematological indices and serum metabolite levels reflect the health status of animals, and in the present study, these parameters were within the normal ranges for healthy calves (Alugongo et al, 2017;Maldonado et al, 2018;Slanzon et al, 2019;D. Wang et al, 2022).…”
Section: Discussionsupporting
confidence: 76%
“…Haematological indices and serum metabolite levels reflect the health status of animals, and in the present study, these parameters were within the normal ranges for healthy calves (Alugongo et al, 2017; Maldonado et al, 2018; Slanzon et al, 2019; D. Wang et al, 2022). The results of the present study showed that HNa and Gln supplementation had no effects on haematological indices and serum metabolites of pre‐weaned calves.…”
Section: Discussionsupporting
confidence: 73%
“…In our research, the chemical composition of the starter feed (Table 3) was consistent with that used in dietary experiments with NaHum additives on heifers conducted by [18] and Raketsky et al (2021) [72]. Raketsky et al (2021) [72] and Crowe et al (2018) [73] emphasized that heifers mature faster than bulls; therefore, to avoid excess fat formation, which is often the reason for culling heifers, they need a specially balanced diet and more careful monitoring.…”
Section: -2-changes In Growth Indicators Of Breeding Heiferssupporting
confidence: 71%
“…Sodium humate inclusion in the diet of breeding heifers effectively decreases diarrhea incidence and improves growth performance in pre-weaned Holstein calves by enhancing their antioxidant and immune status and modulating intestinal microflora [18]. Sodium humate is a macromolecular substance comprising humic acid, which is rich in phenolic hydroxyl and carboxyl groups and has antidiarrheal, antioxidant, and anti-inflammatory properties.…”
mentioning
confidence: 99%
“…This unique biochemistry supports the application of humate as a soil conditioner, supporting soil micro‐organisms, the bioavailability of macro‐ and micro‐ nutrients in soil as well as plant physiology and growth 2 . These same properties also suggest that humate may be a valuable livestock feed additive, with potential effects on nutrient utilisation and animal performance 3 …”
mentioning
confidence: 52%